Efficacy and Treatment-Related Adverse Events of Romidepsin in PTCL Clinical Studies: A Systematic Review and Meta-Analysis - Jun Du (Frontiers Media S.A., 2021)
Background: Peripheral T-cell lymphoma (PTCL) is an extensive class of biologically and clinically heterogeneous diseases with dismal outcomes. The histone deacetylase inhibitor (HDACi) romidepsin was approved for relapsed and refractory (R/R-PTCL) in 2011. This meta-analysis was performed to assess the efficacy and safety of romidepsin in PTCL.Methods: We searched for articles on the HDAC inhibitor romidepsin in the treatment of PTCL in Embase, Web of Science, and PubMed. The methodology is further detailed in PROSPERO (CRD42020213651, CRD42020213553). The 2-year overall survival (OS), 2-year progression-free survival (PFS), and their corresponding to 95% confidence intervals (CIs) were measured. Besides, corresponding 95% CIs were pooled for the complete response (CR), partial response (PR), duration of response (DoR), and risk of adverse events (AEs).Results: Eleven studies containing 388 patients were incorporated into the quantitative synthesis, of which R/R-PTCL patients were the dominant portion, accounting for 94.3% (366/388). For all studies, the CR rate was 20% (95% CI, 13–27%, random effects model), and the PR rate was 18% (95% CI, 12–25%, random effects model). The 2-year OS was 48% (95% CI, 38–59%, fixed effects model), and the 2-year PFS was 17% (95% CI, 13–21%, fixed effects model). There were no significant differences between romidepsin monotherapy and romidepsin plus additional drugs. Hematological toxicities, such as lymphopenia and granulocytopenia, remained the most continually happening grade 3 or higher AEs, accounting for 46 and 28%, respectively. None of the studies reported any drug-related mortality.Conclusions: Considering that most of the included patients had R/R-PTCL, the addition of romidepsin significantly enhance the efficacy. And AEs were tolerable as the grade 3/4 AEs in romidepsin monotherapy was 7% (95% CI, 6–8%). It is imperative to further expand the first-line application of romidepsin and carry out personalized therapy based on epigenomics, which will improve the survival of PTCL patients.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020213651 and https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020213553.